Guaianolides from Artemisia codonocephala suppress interleukine-1β secretion in macrophages. (December 2021) - Wang, Qiaoqiao; Zhang, Tian; Ke, Chang-Qiang; Tang, Chunping; Yao, Sheng; Lin, Ligen; Ye, Yang
Abstract: Sesquiterpene lactones supply a variety of scaffolds for the development of anti-inflammatory drugs. In this study, eight undescribed guaianolides, i.e., lavandolides A‒ H, were isolated from the whole plants of Artemisia codonocephala, together with five known analogues. Their planar structures and relative configurations were elucidated by spectroscopic measurements, and their absolute configurations were determined by electronic circulardichroism spectra and single crystal X-ray diffraction experiments. The nitric oxide inhibitory effect of all the isolates was assessed on lipopolysaccharide stimulated THP-1 macrophages. Lavandolide D showed a potent inhibitory effect on NO production, with IC50 values of 3.31 ± 0.74 μ M. Furthermore, lavandolide D inhibited NOD-, LRR- and pyrin domain-containing protein 3 inflammasome-mediated interleukin-1β production through activating autophagy. Graphical abstract: Image 1 Highlights: Eight undescribed guaianolides were isolated from Artemisia lavandulifolia. Most absolute configurations were confirmed by single crystal X-ray diffraction. Lavandolide D shows inhibition on NO production with a IC50 value of 3.31 μ M. Lavandolide D inhibits NLRP3-mediated IL-1β production by activating autophagy.